PENGARUH STRUKTUR MODAL DAN INFLASI TERHADAP PROFITABILITAS PERUSAHAAN CONSUMER NON-CYCLICALS DI INDONESIA PERIODE 2022 - 2024 - Albani Gustian Suherman; Egi Arvian Firmansyah (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This research assesses the extent to which two capital structure indicators, Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), and the macroeconomic variable of inflation collectively shape the profitability of consumer non-cyclicals sector firms listed on the Indonesia Stock Exchange (IDX). The observation period spans 2022 through 2024. Through purposive sampling, 102 firms were selected, forming a balanced panel of 306 firms data points. Heteroskedasticity was addressed using the Fixed Effect Model augmented with Clustered Robust Standard Error estimation. Partial test results show that DER exerts a negative and statistically significant effect on ROE, while neither DAR nor inflation produces a meaningful individual effect. The simultaneous test confirms that all three variables jointly explain variations in ROE. Robustness checks incorporating firm size and revenue growth as supplementary controls yield consistent conclusions. Overall, the findings highlight that debt leverage surpassing the optimal point, particularly as measured by DER, is the predominant factor suppressing profitability in this sector.